Stress concentration factors of CFRP-reinforced tubular K-joints via Zero Point Structural Stress Approach. (July 2022) - Mohamed, H.S.; Zhang, L.; Shao, Y.B.; Yang, X.S.; Shaheen, M.A.; Suleiman, M.F.
Abstract: The SCFs of the tubular K-joints reinforced with carbon fiber reinforced polymer (CFRP) were computed using the zero-point structural stress (ZPSS) method. After employing several sets of data to verify the proposed finite element (FE) model, a comparison between the ZPSS and hot spot stress (HSS) approaches was established. The results indicate that ZPSS approach is superior to HSS approach in calculating the SCFs. Then 319 models were established to parametrically assess the efficiency of the CFRP strengthening on the fatigue performance of the tubular K-joints. The findings show that the CFRP strengthening dramatically minimizes SCFs at the weld toe's heel, saddle, and crown. In addition, the orientation of the first layer of the CFRP laminate and the layups had significant effects on the SCFs along the weld toe. Moreover, three precise equations were proposed to determine the SCFs of CFRP-reinforced K-joints at the heel, saddle, and crown, respectively. Highlights: Stress Concentration Factors (SCF) of CFRP-reinforced tubular K-joints was evaluated. Zero Point Structural Stress Approach (ZPSS) was employed to determine the value of the SCFs. A comparison between the HSS brooch and ZPSS abroach in calculating the SCFs was conducted. Parametric equations to predict the SCFs of CFRP-reinforced tubular K-joints was established.